2022
DOI: 10.3390/ijms23062994
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Innate Immune Response of Human Fetal Membranes against Escherichia coli Choriodecidual Infection

Abstract: An infectious process into the uterine cavity represents a major endangered condition that compromises the immune privilege of the maternal–fetal unit and increases the risk for preterm birth (PTB) and premature rupture of membranes (PROM). Fetal membranes are active secretors of antimicrobial peptides (AMP), which limit bacterial growth, such as Escherichia coli. Nevertheless, the antibacterial responses displayed by chorioamniotic membranes against a choriodecidual E. coli infection have been briefly studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Indeed, immune defense against infection involves complex mechanisms and, undoubtedly, a critical one is the synthesis of antimicrobial peptides [ 76 ]. Among them, HBDs are the most studied group of microbicidal peptides in the maternal–fetal interface [ 77 , 78 , 79 , 80 ]. In vitro and in vivo experiments have demonstrated that a high glucose concentration in sera or culture media diminished the production of HBDs [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immune defense against infection involves complex mechanisms and, undoubtedly, a critical one is the synthesis of antimicrobial peptides [ 76 ]. Among them, HBDs are the most studied group of microbicidal peptides in the maternal–fetal interface [ 77 , 78 , 79 , 80 ]. In vitro and in vivo experiments have demonstrated that a high glucose concentration in sera or culture media diminished the production of HBDs [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest expression has been observed for HBD-3, which is a dominant defensin in the amniotic epithelium. In vitro studies on cultured fetal membranes showed increased production of HNP-1 to -3 and HBD-1 and -2 in the presence of E. coli infection [ 123 ].…”
Section: Amp Sources In the Intrauterine Environment The Fetus And Th...mentioning
confidence: 99%
“…Cathelicidin LL-37 levels remain relatively unchanged throughout uncomplicated pregnancies ( Figure 3 ) [ 124 , 125 ]. Some researchers failed to demonstrate the presence of either HBD 2 or LL-37 in the AF of uncomplicated pregnancies, probably because the expression of these AMPs is inducible [ 106 , 123 ].…”
Section: Amp Sources In the Intrauterine Environment The Fetus And Th...mentioning
confidence: 99%
See 2 more Smart Citations